Manajemen Pondok Pesantren Dalam Meningkatkan Keterampilan Berdakwah Di Pondok Pesantren Modern Dan Tahfidz Al - Ikhwan Assalam Serapuh ABC Kecamatan Tanjung Pura - Rani Febriyanni, Yulia Kasti, Muhammad Saleh, (Invention: Journal Research and Education Studies, 2022)
This research is a qualitative research. With this type of field research, this is done to explain various kinds of problems related to the subject matter being studied. Sources of data in this study obtained by means of observation, interviews and documentation. The results showed from the results of interviews with informants regarding the implementation of the management of the Al Ikhwan Assalam Islamic Boarding School has been going well. The application of management in the management of Islamic boarding schools includes various aspects such as aspects of education, aspects of worship, economic aspects, aspects of da'wah, aspects of social media, aspects of cooperative relationships. In carrying out the management planning of Islamic boarding schools, it is carried out at the beginning of the new academic year by compiling a work program to be carried out, the organization carried out has a management structure that includes aspects of their respective fields, in the implementation alone conducted in accordance with plan which has been made at the beginning and with time according to their respective aspects, while the self-evaluation is carried out at the end of the new school year to assess activities that are already running and lack of activities to become suggestions for further activities. Improvement in students' da'wah skills at Pondok Pesantren Al Ikhwan Assalam Serapuh ABC is done by applying the elements of management. Namely da'wah planning, organization of da'wah, implementation of da'wah, supervision of da'wah and evaluation of da'wah. Some of the supporting factors in da'wah management activities are the existence of a library as a reference source for the library. There is responsibility and loyalty from the administrators and Ustadz of Al Ikhwan Assalam Islamic Boarding School Serapuh ABC in fostering the da'wah of students . In addition to supporting factors, there are inhibiting factors, namely the activities carried out are sometimes unsatisfactory, due to limited references from the students. Limitations Inadequate reference sources Weak use of technology to develop student excellence values because students are not allowed to use cell phones in Islamic boarding schools.